2005
DOI: 10.1152/ajpheart.00534.2005
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of small-conductance Ca2+-activated K+channels SK1, SK2, and SK3 in mouse atrial and ventricular myocytes

Abstract: Small-conductance Ca2+-activated K+ channels (SK channels, KCa channels) have been reported in excitable cells, where they aid in integrating changes in intracellular Ca2+ with membrane potential. We recently reported for the first time the functional existence of SK2 (KCa2.2) channels in human and mouse cardiac myocytes. Here, we report cloning of SK1 (KCa2.1) and SK3 (KCa2.3) channels from mouse atria and ventricles using RT-PCR. Full-length transcripts and their variants were detected for both SK1 and SK3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
194
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 211 publications
(203 citation statements)
references
References 44 publications
6
194
2
1
Order By: Relevance
“…They mediate the afterhyperpolarization, which ends the action potential [142] . In the periphery, the SK channels are expressed in T-lymphocytes and atrial cells and play an important role in atrial repolarization [143][144][145][146][147][148] . SK1 channels are resistant to apamin [136] , and their unitary conductance varies from 11 to 26 pS depending on the experimental conditions [149][150][151] .…”
Section: The Calcium-activated Potassium Channel Familymentioning
confidence: 99%
“…They mediate the afterhyperpolarization, which ends the action potential [142] . In the periphery, the SK channels are expressed in T-lymphocytes and atrial cells and play an important role in atrial repolarization [143][144][145][146][147][148] . SK1 channels are resistant to apamin [136] , and their unitary conductance varies from 11 to 26 pS depending on the experimental conditions [149][150][151] .…”
Section: The Calcium-activated Potassium Channel Familymentioning
confidence: 99%
“…Specifically, several isoforms of small conductance Ca 2ϩ -activated K ϩ channels (SK or K Ca 2 channels) have been identified that underlie the Ca 2ϩ -activated K ϩ current (I K,Ca ) in human and mouse atrial myocytes (8,9). The SK channels are highly unique in that they are gated solely by changes in intracellular Ca 2ϩ ([Ca 2ϩ ] i ).…”
Section: Ca V 12 (␣ 1c ) L-type Camentioning
confidence: 99%
“…SK channels represent a highly unique family of K ϩ channels, in that they are directly gated by changes in intracellular Ca 2ϩ concentration and hence function to integrate changes in Ca 2ϩ concentration with changes in K ϩ conductance and membrane potentials. SK channels have been shown to mediate afterhyperpolarizations in neurons (9,12,13) and action potential repolarization in cardiac tissues (14,15). Previous studies have provided strong support that ion channels are components of macromolecular complexes containing the main pore-forming and auxiliary subunits interacting with scaffolding and regulatory proteins that are linked to the cytoskeleton (16).…”
mentioning
confidence: 99%